Implementing Corporate Social and Environmental Responsibility Policy in North Minahasa Regency, Indonesia - Donal Tintingon; Sisca Beatrix Kairupan; Steven V. Tarore (JR Education, 2026)
The study examines how the policy is implemented through planning, program execution, coordination, reporting, monitoring, and evaluation, and identifies the determining factors affecting its effectiveness. The original thesis used a descriptive qualitative design and gathered data through interviews, observation, and documentation involving the TJSLP Forum, local government agencies, corporate representatives, and community beneficiaries. This article reorganizes those findings into a full journal manuscript modeled on the structure of a contemporary policy journal article and strengthens the analysis through thesis-based tables and field documentation photographs. The findings show that TJSLP implementation in North Minahasa has moved beyond symbolic regulation but remains suboptimal. In the planning dimension, most programs are still dominated by internal corporate design and are not fully integrated with RPJMD and RKPD priorities. In the implementation dimension, TJSLP activities remain largely charity-oriented and short-term, with limited emphasis on community empowerment and environmental sustainability. In the coordination dimension, the TJSLP Forum already exists as a formal platform, yet company participation, cross-sector synchronization, and community involvement remain uneven. In the reporting and accountability dimension, company compliance is inconsistent, reporting procedures are not standardized, and evaluation is still focused more on outputs than on outcomes and impacts. The determining factors shaping implementation include corporate commitment and compliance, institutional capacity of the TJSLP Forum, weak integration between TJSLP and regional development planning, and limited supervision and accountability mechanisms. The article argues that strengthening operational rules, performance-based reporting, collaborative planning, and institutional capacity is essential if TJSLP is to evolve from a fragmented charity into a strategic instrument of sustainable regional development. The study contributes to public administration literature by demonstrating that local TJSLP policy effectiveness depends not only on legal mandates but also on governance integration, stakeholder commitment, and the institutionalization of collaborative accountability.